2021
DOI: 10.3390/su132112281
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Urban Low-Carbon Sustainability in Four Chinese Cities

Abstract: Practices and research on measuring traditionally urban sustainability abound, therefore the challenge now is related to how the urban carbon issues are included into current measuring methods, thus there is a need to develop methods for measuring urban low-carbon sustainability. In this paper, a simple method, which is based on low-carbon sustainability index, is developed. The overall urban low-carbon sustainability index is the weighted sum of 11 single indices, and each single index is defined as the indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…M. Zhang et al (2021) adopted the low-carbon sustainability index method in a study of four selected Chinese cities. Results showed that all four cities failed the test for sensible low-carbon sustainability rules.…”
Section: Methodsmentioning
confidence: 99%
“…M. Zhang et al (2021) adopted the low-carbon sustainability index method in a study of four selected Chinese cities. Results showed that all four cities failed the test for sensible low-carbon sustainability rules.…”
Section: Methodsmentioning
confidence: 99%
“…Several methods are commonly applied in weighting indicators [22]. As a simple method, this is examined and based on a low-carbon sustainability index [23]. The LCIP criteria reflect many aspects of IPs development toward LCE, and each criterion has relative importance.…”
Section: Comparisionmentioning
confidence: 99%
“…Equation ( 8) converts four multiplicative terms in Equation ( 7) into four additive terms, and each additive term corresponds to the contribution of each factor. Due to the absence of a unique decomposition solution for Equation (8), the average of the polar decompositions was applied to approximate the average of all decompositions [44]. Solving Equation ( 8) with the so-called polar decompositions yields:…”
Section: Structural Decomposition Modelmentioning
confidence: 99%
“…The evaluation and decomposition of low-carbon performance is valuable as it could provide significant information for monitoring and guiding the process of low-carbon development [8,9]. In this regard, carbon emission intensity (CEI), referring to the ratio of CO 2 emissions to GDP, is an index that reflects the level of low-carbon development in a country or region [10].…”
Section: Introductionmentioning
confidence: 99%